2017
DOI: 10.1159/000474945
|View full text |Cite
|
Sign up to set email alerts
|

The First Case of Kernohan-Woltman Notch Phenomenon Caused by Epidural Hematoma in a Pediatric Patient

Abstract: Kernohan-Woltman notch phenomenon (KWNP) is an ipsilateral motor weakness due to compression of the contralateral cerebral peduncle. Most of the KWNP cases reported have been due to subdural hematomas, intracranial space-occupying lesions, and spontaneous bleeding of vascular malformations. In this study, we present the first pediatric case of KWNP caused by a traumatic epidural hematoma. Although subdural hematomas are the most frequent reason for KWNP, epidural hematomas may cause paradoxical ipsilateral sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Reports concerning patients suffering from KWNP ranged from 1990 to 2020 [2][3][4][5][6][7][8][9][10][13][14][15]17,[19][20][21]23,[26][27][28][29][30][33][34][35][36][37][39][40][41][43][44][45][46]49,50,[52][53][54][55][59][60][61][62][63] . The database research yielded 220 articles and 149 after removal of duplicates.…”
Section: Database Researchmentioning
confidence: 99%
“…Reports concerning patients suffering from KWNP ranged from 1990 to 2020 [2][3][4][5][6][7][8][9][10][13][14][15]17,[19][20][21]23,[26][27][28][29][30][33][34][35][36][37][39][40][41][43][44][45][46]49,50,[52][53][54][55][59][60][61][62][63] . The database research yielded 220 articles and 149 after removal of duplicates.…”
Section: Database Researchmentioning
confidence: 99%
“…6 For HICH patients with supratentorial hematoma volume ≥ 20mL or infratentorial hematoma volume ≥ 10 mL, surgery is still the primary choice. 7 With the development of neuroendoscopy, the application of brain microsurgery is becoming increasingly mature, and most intracranial space-occupying lesions can be removed by microsurgery. 8 Stereotactic technology was firstly reported to be used in the treatment of HICH in 1978, with the Patients with Hypertensive Intracerebral Hemorrhage…”
Section: Discussionmentioning
confidence: 99%
“…1,7 A few studies have reported the association of the Kernohan-Woltman notch phenomenon with epidural hematoma. 8 Evaluation with brain CT would be sufficient in most patients with a severe traumatic head injury, and the decision for surgical intervention is usually made on the basis of the neurological condition of the patient and brain CT result. Most MRI studies are performed after the surgical intervention.…”
Section: Discussionmentioning
confidence: 99%